Empowering An Integrated Approach : How Does Teacher Preparing Indonesian Language Planning? - Muhammad Asdam; Asdar Asdar; Asia M Asia M (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to explore the application of an integrated approach in preparing learning plans for Indonesian language subjects at the senior high school level. The research method was qualitative in the form of a case study carried out at some schools in Makassar. The subjects of this research were Indonesian language teachers who were determined purposively. Data collection methods were observation, interviews, and documentation. Data were analyzed using (1) reduction, (2) presentation, and (3) verification techniques. The findings show that empowering the integrated approach always begins, and this was dominated by the speaking aspect rather than the other skills such as reading, writing, and listening skills. On the other hand, linguistic aspects are least programmed by Indonesian language teachers. Linguistic aspects are never combined with literature, even though it is very interesting to teach at the high school level on a multi-ethnic basis. It can be concluded that the Indonesian language is taught by using an integrated approach, which can reshape the students’ speaking competency. This approach is implemented in the lesson plan to enhance the Indonesian learning process.